Response of biodegradation characteristics of unacclimated activated sludge to moderate pressure in a batch reactor. (April 2016) - Xu, Rui-Xiao; Li, Bing; Zhang, Yong; Si, Ling; Zhang, Xian-Qiu; Xie, Biao
Abstract: This study was aimed to investigate the effect of moderate pressure on unacclimated activated sludge. Process of organic degradation, variation of carbon dioxide (CO2 ) concentration of off-gas and characteristics of extracellular polymeric substances (EPS) of activated sludge were analyzed using pressure-atmospheric comparative experiments in bench-scale batch reactors. It was found that moderate pressure increased the degradation rate more dramatically when the biological process ran under a higher organic load with much more oxygen demand, which illuminated that applications of the pressurized method to high concentration organic wastewaters would be more reasonable and practicable. High oxygen transfer impetus increased utilization of oxygen which not only promoted the biodegradation of organics in wastewater, but also led to more EPS consumption in activated sludge. CO2 concentration of off-gas was lower in the earlier stage due to CO2 being pressed into the liquid phase and converted into inorganic carbon (IC). More CO2 emission was observed during the pressurized aerobic process 160 min later. EPS in pressurized reactor was much lower, which may be an important way of sludge reduction by pressurized technology. Highlights: Process of TOC, DO, CO2 concentration of off-gas and EPS were monitored. Effect of pressurizing was evaluated by degradation rate. Application of pressurizing under high organic load is reasonable and practicable. More oxygen expenditure leads to more EPS consumption.